PENGARUH KOMPETENSI PEDAGOGIK, KOMPETENSI PROFESIONAL, DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI LEMBAGA PENDIDIKAN ISLAM HIDAYATUL UMMAH MAGETAN - Azzahra Hafizhahtul Azizah; Ike Kusdyah Rachmawati; Yunus Handoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of pedagogical competence, professional competence, and work motivation on teacher teaching performance at Hidayatul Ummah Islamic Educational Institution (LPI) Magetan. The research method employed a quantitative approach with linear regression analysis on41 reacher respondenst. The result showed that simultaneously, the three variable significantly influenced teacher performance. However, partially, it was found that only professional ompetence had a positive and significant effect on teacher performance. Incontrast, pedagogical competence and work motivation were found tho have no significant partial effect on teacher performance at the institution. This indicates that deep mastery of subject matter and professional development are the most decisive factors in determining the quality of teacher perfoemance at LPI Hidayatul Ummah Magetan compared to other factors in this study.